DP3 signal as a neuro-indictor for attentional processing of stereoscopic contents in varied depths within the ‘comfort zone’ - Ye, Peng; Wu, Xiang; Gao, Dingguo; Deng, Shaozhi; Xu, Ningsheng; Chen, Jun (Displays, 2020)
•S3D contents within traditional ‘comfort zone’ were equal comfortable subjectively.•DP3 signal for processing S3D contents was obtained for different disparities.•DP3 latency monotonically delayed for larger disparity within the ‘comfort zone’. When viewing stereoscopic 3D (S3D) displays, excessive binocular disparity is one of the major sources for the induced visual fatigue. Limiting the disparity within a certain range termed ‘comfort zone’ is a useful approach to alleviate the negative impact of viewing the S3D displays. Using the event-related potential (ERP) approach, we have previously showed that the differential P3 (DP3) signal evoked in an oddball task could be a useful neural indicator of the involvement of high-level cognitive functions in viewing S3D contents within the comfort zone compared to viewing 2D contents, despite of the similar subjective comfort of viewing experience for the two display conditions. It remains unclear whether the DP3 signal is sensitive enough for examination of the high-level processing when viewing S3D contents in different disparities within the comfort zone. Here, the DP3 signals were recorded while subjects performed an oddball task presented in S3D modality for three disparities (0.15, 0.45 and 0.76 arcdeg) within the comfort zone. Whereas the oddball task was of similar comfort by subjective measurement for different disparities, the DP3 signal showed monotonic delay in latency for increasing disparity, suggesting the capability of the DP3 signal for establishing a ‘cognitive comfort zone’ in terms of the high-level cognitive functions.